The principle of alternation of power: A new strategy for achieving public utility effectiveness in Algeria - Rital, Salah (The International tax journal, 2025)
Public utilities are considered among the most important legal mechanisms relied upon by the state to satisfy general needs. For these services to be of high quality and effective, they must be managed according to international principles and standards that ensure greater transparency and democracy. The principle of alternation of power represents an aspect of democratic practice. The more this principle is embodied in the management of public utilities, the more effective and functional these utilities become. State policy has recently focused on materializing this through various legislations, starting with the 2020 constitutional amendment.